Dry gas seat simulation with different spiral tapered grooves / Ibrahim Shahin ... [et al.] - Shahin, Ibrahim (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2014)
The flow and performance analysis for a dry gas seal (DGS) with a standard and tapered spiral grooves is developed using a verified FLUENT CFD model. A comprehensive analysis is proposed to resolve the effect of modifying the seal grooves geometry on gas film pressure distribution and the seal performance. The effect of the fluid state and the rotational speed on the gas seal performance and internal flow field are studied and presented. The fluid state effect on the gas seal internal flow and performance is studied, Laminar and turbulent flow with RNG K-e turbulence model and LES is examined for the same geometrical and operating conditions. Also different rotational speed effect on gas seal performance is examined for 0, 2500, 5000, 7500 and 10380 rpm. Three taper spiral grooves are studied each with three different angles, including taper grooves in the radial, circumferential and combined radial-circumferential directions. The laminar flow simulation for the dry gas seal agree well with the experimental results more than the turbulent flow simulation which overestimate the pressure distribution inside the seal. The results indicate that as the rotational speed increase the seal open force and leakage increase. The use of tapered type spiral groove causes a reduction in the seal open force and the leakage rate. Increasing the angle of radial taper groove reduces the temperature distribution inside the gas film. The Reduction in seal open force and leakage rate is higher when use combined Radial-circumferential taper more than radial and circumferential taper used.